Cardiac screening of young athletes: a practical approach to sudden cardiac death prevention - Dhutia, H.; MacLachlan, H. (Current Treatment Options in Cardiovascular Medicine, 2018)
Purpose of review: We aim to report on the current status of cardiovascular screening of athletes worldwide and review the up-to-date evidence for its efficacy in reducing sudden cardiac death in young athletes. Recent findings: A large proportion of sudden cardiac death in young individuals and athletes occurs during rest with sudden arrhythmic death syndrome being recognised as the leading cause. The international recommendations for ECG interpretation have reduced the false-positive ECG rate to 3% and reduced the cost of screening by 25% without compromising the sensitivity to identify serious disease. There are some quality control issues that have been recently identified including the necessity for further training to guide physicians involved in screening young athletes. Summary: Improvements in our understanding of young sudden cardiac death and ECG interpretation guideline modification to further differentiate physiological ECG patterns from those that may represent underlying disease have significantly improved the efficacy of screening to levels that may make screening more attractive and feasible to sporting organisations as a complementary strategy to increased availability of automated external defibrillators to reduce the overall burden of young sudden cardiac death.